Rasio Efektivitas dan Elastisitas Pemungutan Pajak Daerah di Kota Kendari - Indra Hariyanto; Wa Ode Fitri Auliya Azzahra; Al Kusman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to (1) show empirical evidence of the effectiveness of hotel and restaurant taxes, and entertainment taxes in Kendari City for the 2016-2020 period. (2) Shows empirical evidence of how the elasticity of hotel and restaurant taxes, and entertainment taxes in Kendari City for the 2016-2020 period. This study uses a quantitative descriptive method. The data collection method used in this research is documentation and literature study. The type of data used is secondary data, while the data source is obtained through BPKAD and BPS Kendari City. The results of the study show that the ratio of the effectiveness of collecting hotel and restaurant taxes, and entertainment taxes from 2016-2018 fluctuates but is still within the very effective criteria. The elasticity ratio of hotel and restaurant tax collection and entertainment tax from 2016-2018 runs elastic on average, although in 2018 it shows inelasticity.